Pengaruh Model Pembelajaran Problem Solving terhadap Kemampuan Menulis Teks Anekdot pada Siswa Kelas X SMK-1 Swasta Taman Siswa Pematangsiantar - Damay Gresia Butar-Butar; Jumaria Sirait; Junifer Siregar (Medan Resource Center, 2022)
This study aims to determine: (1) the ability to write anecdotal texts before using the problem solving learning model in class X SMK-1 Private Tamansiswa Pematangsiantar. (2) The ability to write anecdotal texts after using problem solving learning models in class X SMK-1 Tamansiswa Pematangsiantar Private. (3) The effect of the problem solving model on the ability to write anecdotal texts in class X SMK-1 Tamansiswa Pematangsiantar Private. The method used in this research is a quantitative-experimental research method. The type of experimental research used in this study was pre-experimental designs, the research design used in this study was a one group pretest-posttest design. The results of this study include: (1) The results of the initial test ability (pre-test) in the skills of writing anecdotal texts in class X SMK-1 Tamansiswa Pematangsiantar Private before applying the problem solving learning model obtained an average value of 37.72. From the results (pre-test) it was obtained that the students' ability to write anecdotal texts had not reached the KKM target of 70. (2) The results of the final test (post-test) skills in writing anecdotal texts in class X SMK-1 Private Tamansiswa Pematangsiantar After applying the problem solving learning model, the average value was 72.12. From the results (post-test) it was obtained that the students' ability in writing anecdotal texts had reached the KKM target of 70. (3) The analysis that has been carried out and has been tested statistically is that tcount is greater than ttable (5.07 > 1.69) causing H0 to be rejected and Ha to be accepted. Thus, it can be concluded that there is an effect of problem solving learning model on the ability to write anecdotal texts in class X SMK-1 Private Tamansiswa Pematangsiantar.